Combating the COVID-19 Pandemic: Experience of a Tertiary Care Children Hospital in Dhaka, Bangladesh - Ghosh, Nobo Krishna; Afroze, Sharmin; Ahmed, Erfan (International Journal of Human and Health Sciences (IJHHS), 2023)
Background: Corona virus disease is a global health threat since December 2019 which was declared a pandemic in March 2020. Objective: This study was undertaken to address various measures initiated during the pandemic in the Dr. M R Khan Shishu (Children) Hospital, a tertiary level childcare hospital in Dhaka, Bangladesh. Methods: This crosssectional, observational study was conducted over a period of 9 months from March 2020 to November 2020. Necessary steps implemented during ‘lock down’ Phase were tabulated. Sample was collected from patients as well as Health care providers with sign/ symptoms of COVID-19 disease. Verified reports were analyzed to observe the prevalence and trends of corona virus affected population. Results: Improvement of situation was observed following modification of the infrastructure as well as delivery of service to people. Hand sanitization, COVID sampling, PPE availability and isolation facility were improved from baseline to 100% during the study period. A total of 736 cases were tested with 246 Positive cases having male predominance (64%). Less than two years children infected with COVID-19 required admission more comparing to other children. Total 102 health care providers were tested among them 50% were found positive for COVID-19. Conclusion: Throughout the pandemic, Dr. M R Khan Shishu Hospital & ICH, have taken all affordable measures to combat the situation with a positive outcome. Moreover, hundred percent testing facilities for COVID-19 enabled us to diagnose significant portion of health care providers as well as patients and to take appropriate measure in management. International Journal of Human and Health Sciences Vol. 07 No. 01 Jan’22 Page: 60-66